Common Rail System for GDI Engines Modelling, Identification, and Control - Fiengo, Giovanni; di Gaeta, Alessandro; Palladino, Angelo; Giglio, Veniero; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Progressive reductions in vehicle emission requirements have forced the automotive industry to invest in research and development of alternative control strategies. Continual control action exerted by a dedicated electronic control unit ensures that best performance in terms of pollutant emissions and power density is married with driveability and diagnostics. Gasoline direct injection (GDI) engine technology is a way to attain these goals. This brief describes the functioning of a GDI engine equipped with a common rail (CR) system, and the devices necessary to run test-bench experiments in detail. The text should prove instructive to researchers in engine control and students are recommended to this brief as their first approach to this technology. Later chapters of the brief relate an innovative strategy designed to assist with the engine management system; injection pressure regulation for fuel pressure stabilization in the CR fuel line is proposed and validated by experiment. The resulting control scheme is composed of a feedback integral action and a static model-based feed-forward action, the gains of which are scheduled as a function of fundamental plant parameters. The tuning of closed-loop performance is supported by an analysis of the phase-margin and the sensitivity function. Experimental results confirm the effectiveness of the control algorithm in regulating the mean-value rail pressure independently from engine working conditions (engine speed and time of injection) with limited design effort.
The Common Rail System -- Mathematical Modeling of Pressure Dynamics -- GDI Injector Model -- Control Design -- Injection Time Management.
Keywords: Engineering; Engineering; Control; Automotive Engineering; Energy Systems